HABITUS BERBAHASA DAN RESISTENSI BUDAYA GENERASI MUDA DI KOTA GORONTALO - Abdul Haris M Madina; Rahmatiah Rahmatiah; Fidya Ramadhani Abdullah Dede; Faradiba Azzahra; Fahmid Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
Regional languages are a vital instrument in maintaining the collective identity of the community because they contain historical values, collective memory, and deep local wisdom. This study aims to analyze the dynamics of language habitus and forms of cultural resistance among the young generation in Gorontalo City as a response to the pressure of globalization and national language hegemony. Using a descriptive qualitative approach, this study explored data through participatory observation, in-depth interviews, and narrative data screening of research subjects consisting of students and students. The results of the study show that the use of the Gorontalo language experiences a sharp segregation of the domain; This language remains a primary habitus in the domestic and customary environment, but it is marginalized in the professional realm and digital media due to the low symbolic capital compared to the Indonesian language. However, a form of cultural resistance was found through the practice of creative code transfer on social media and participation in language revitalization programs. The research concludes that the sustainability of the Gorontalo language depends on the reconstruction of habitus that places the regional language as a cultural capital that is relevant to the development of the times. Synergy between government policies and the creative community is needed to ensure that local identities continue to exist in the global ecosystem.